OUTER LIMITS OF CONTINENTAL SHELF IN THE ARCTIC OCEAN: POTENTIAL OVERLAPPING CLAIMS - Liliansa, Dita (UI Scholars Hub, 2015)
To legally exercise its sovereign rights over extended continental shelf, coastal States have to obtain recommendation from the Commission on the Limits of the Continental Shelf by submitting information on the limits of its extended continental shelf to the Commission. In some cases, such submission overlaps with other submission which leads to deferred submissions. This paper will address some potential overlapping submissions in respect of the Arctic Ocean which is carried out through a normative legal study. At the end, this paper suggests that Arctic coastal States may agree on establishing a joint submission to avoid any overlapping submissions in the Arctic Ocean.